Ensayo en época invernal de un horno solar con reflector inferior y comparación con un modelo convencional - Lucchini, Juan M. (2016)
This work shows the performance study of a solar box cooker to which a lower reflector has been added, making a comparison with a similar normal cooker. The main goal of the research was to analyze if it is possible to achieve adequate conditions for food cooking in winter time, when the solar altitude is low, which causes that the incidence of sun rays diminish over the cooker aperture area. Both cookers were measured in parallel, by using the procedure proposed by the Solar Food Cooking Ibero-American Network. The design and fabrication process of the prototype is described. The results showed that the addition of a lower reflector allow the cooker to reach and maintain the boiling of a indicated water mass for more than 90 minutes. The performed measurements of temperature and solar radiation are shown by means of plots and the results are summarized in tables.